2016
DOI: 10.4293/jsls.2016.00043
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Total Extraperitoneal Hernia Repair Outcomes

Abstract: Background and Objectives:Laparoscopic inguinal hernia repair has become increasingly popular as an alternative to open surgery. The purpose of this study was to evaluate the safety and effectiveness of the laparoscopic total extraperitoneal procedure with the use of staple fixation and polypropylene mesh.Methods:A retrospective chart review examined outcomes of 1240 laparoscopic hernia operations in 783 patients, focusing on intraoperative and early postoperative complications, pain, and time until return to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 31 publications
1
27
1
Order By: Relevance
“…By meta-analysis, we found it was a tendency for patients under SA to experience more urinary retention than GA, in agreement with the most recent guidelines concluding that urinary retention might be more frequent following regional anesthesia [21]. Moreover, Reiner and his colleagues found that the age of the patients with urinary retention was significantly higher than patients without urinary retention, and suggested that urinary retention is seen more often in elderly patients [22]. Another study demonstrated that using short-acting agent, lidocaine, for SA virtually eliminates problems with urinary retention that occurs with long-acting SA agents [3].…”
Section: Discussionsupporting
confidence: 88%
“…By meta-analysis, we found it was a tendency for patients under SA to experience more urinary retention than GA, in agreement with the most recent guidelines concluding that urinary retention might be more frequent following regional anesthesia [21]. Moreover, Reiner and his colleagues found that the age of the patients with urinary retention was significantly higher than patients without urinary retention, and suggested that urinary retention is seen more often in elderly patients [22]. Another study demonstrated that using short-acting agent, lidocaine, for SA virtually eliminates problems with urinary retention that occurs with long-acting SA agents [3].…”
Section: Discussionsupporting
confidence: 88%
“…15 Reiner MA et al performed a retrospective chart review and examined outcomes of 1240 laparoscopic hernia operations in 783 patients, focusing on intra-operative and early postoperative complications, pain, and time until return to work and normal physical activities and found that patients took an average of 3.0 days (median, 3.0; range, 1-41) to return to routine work and significant physical activity (office work) took an average of 3.8 days (median, 3.0; range, 0-28). 16 Compared to present findings, the time to return to normal routine activities and pain scores was less in triangular TEP technique with The different quality of life (QOL) outcomes measured in Carolina comfort scale (CCS) viz. pain, movement limitation and sensation of mesh decreased with time in the 6-month follow up period.…”
Section: Discussioncontrasting
confidence: 83%
“… 18 However, our laparoscopic repair durations were shorter than those reported in the literature. 20 The duration was longer in the TEP-SA group than in TEP-GA ( P <0.001). This might be because of the prolonged anesthesia used in SA.…”
Section: Discussionmentioning
confidence: 91%